Sustainable Supply Chain Odyssey: Exploring The Interplay Of Green Technology, Green Transportation, and Green Logistics Digitalization On Green Supply Chain Performance - Agus Purnomo; Muhammad Ardhya Bisma; Syafrianita Syafrianita (Dinasti Publisher, 2025)
The rapid expansion of the courier service industry in Indonesia has resulted in heightened delivery activities, contributing to elevated carbon emissions and diminished logistics efficiency, particularly in last-mile delivery. This situation emphasizes the urgent need for the development of green supply chain strategies that are predicated not only on environmentally sustainable technologies and transportation but also on the support of logistics digitalization. This study seeks to analyze the impacts of Green Technology (GTH) and Green Transportation (GTP) on Green Supply Chain Performance (GSP), while also assessing the mediating role of Green Logistics Digitalization (GLD). A quantitative approach was employed through an explanatory survey utilizing a cross-sectional design. Data were gathered from 341 supervisors of courier companies across eight major provinces in Indonesia and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The findings indicate that both GTH and GTP significantly affect GSP, both directly and indirectly through GLD. GTP exhibited the strongest path coefficient (β = 0.462), followed by GTH (β = 0.350) and GLD (β = 0.295). These results extend the Natural Resource-Based View (NRBV) by incorporating digitalization as a strategic environmental capability. Practically, the study advocates for integrated investment in green technologies, sustainable transportation, and digital infrastructure as a key strategy to improve green supply chain performance within the courier industry.